PENGARUH BUDAYA ORGANISASI DAN KESELAMATAN KERJA TERHADAP KINERJA MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Andriyastuti Suratman; Lilis Supriyantiningsih (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2019)
This study discusses about the influence of organizational culture andwork safety on performance with job satisfaction as an intervening variable in Vocational High School 1 Bawang. This is a quantitative research by using questioner as a tool to collect data. The data collection technique used census technique with questionnaire as instrument. This research supported by 103 respondens of 114 teachers totally in Vocational High School 1 Bawang. Data analysis using SPSS 23, including multiple linear regression analysis and path analysis with Sobel analysis.The result of the research are; there is an influence of organizational culture, work safety on the job satisfaction partially, there is an influence of organizational culture, work safety, and job satisfaction on the performance partially, and there is an influence of organizational culture and work safety on performance with job satisfaction as intervening variable. All coefficients are positive values that show a positive influence except the effect of safety on the performance that have negative coefficients numbers.